2021
DOI: 10.3389/fpubh.2021.669958
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Somatic Complaints, and Their Relation to Negative Psychosocial Factors in a Sample of Swedish High School Students

Abstract: Background: Adolescence is a period in life characterized by major neurobiological, physiological, and psychological changes. Those changes may give rise to worsened mental health and an increased prevalence of somatic complaints combined with a negative psychosocial environment. Rapid changes in society, which may also affect young people in several ways, call for a renewed screening of today's adolescents' mental and somatic well-being.Aim: The present study's primary aim was to measure the level of self-rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…Being a girl tripled the risk of reporting increased levels of depression and paranoid ideation during the COVID-19 pandemic in Morocco. Similar results have been found by previous studies carried out before the announcement of the COVID-19 pandemic in Moroccan, Swedish, and Israeli adolescent samples (25,26,101); these results reinforce the conclusion that Moroccan adolescents already reported the worst mental health profile before the COVID-19 pandemic, represented by their higher depression and paranoid ideation scores compared with adolescents from other countries and confirm the feminine trait of mental health problems, as discussed above.…”
Section: Risk and Protective Factors During The Covid-19 Pandemicsupporting
confidence: 91%
See 3 more Smart Citations
“…Being a girl tripled the risk of reporting increased levels of depression and paranoid ideation during the COVID-19 pandemic in Morocco. Similar results have been found by previous studies carried out before the announcement of the COVID-19 pandemic in Moroccan, Swedish, and Israeli adolescent samples (25,26,101); these results reinforce the conclusion that Moroccan adolescents already reported the worst mental health profile before the COVID-19 pandemic, represented by their higher depression and paranoid ideation scores compared with adolescents from other countries and confirm the feminine trait of mental health problems, as discussed above.…”
Section: Risk and Protective Factors During The Covid-19 Pandemicsupporting
confidence: 91%
“…No association was found between parental substance use problems and depression/paranoid ideation symptoms during the COVID-19 pandemic among Moroccan adolescents; in contrast, a recent study showed that Swedish adolescents who reported parental substance use problems scored significantly higher in the PSY, PAR, DEP, and ANX dimensions of the BSI (26). In addition to the Islamic religion, which prohibits the consumption of drugs and alcohol, this non-association between parental substance use problems and the mental health problems diagnosed during the COVID-19 pandemic in the Moroccan adolescent sample can be related to the traffic restrictions required during the COVID-19 pandemic period, which contributed to reducing access to these substances, and therefore, the decrease in their consumption by parents.…”
Section: Risk and Protective Factors During The Covid-19 Pandemicmentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, we believe that the gender-specific results did not emerge from the uneven gender representation in our sample. Instead, the higher levels of stress, psychological distress, and mental health complaints in female adolescents compared to male adolescents seems to be a consistent finding in different cultures [25][26][27][28][29]. It is hypothesized that a higher level of anxiety and perceived stress in female adolescents originates from the higher demands placed on them in different arenas of life, such as family and school [30,31].…”
Section: Covid-19 Restrictions' Impact On Adolescent Mental Health Behaviors and Psychological Functioningmentioning
confidence: 98%